História e memória : licenciatura em história a distância na Universidade Federal de Sergipe (2005-2014) - Souza Júnior, Carlos Menezes de (2019)
The present study analyzes, from a historical point of view, the trajectory of the history under graduated course in the distance learning modality (EAD) of Federal University of Sergipe (UFS). It was mainly through the oral narratives from enrolled subjects, focusing on the value, on the speech, and on the pedagogical practices constructed with and between them during the nine years of its operation, since its creation (2005). In addition to oral sources, laws, reports, resolutions, pedagogical projects of the course, covenants, among other documents collected at CESAD and on official websites were used. From the methodological point of view, the assumptions of oral history as technique were used. The narratives were collected through 14 interviews scheduled, transcribed and processed, from graduates, managers and tutor teachers involved in the training. The creation of a degree in History at EAD at UFS was based on the assumptions and curricular elements of the courses at the institution, thus disregarding the differences between the two educational modalities, which has caused numerous challenges. Of all the points raised by the narratives were: the modality itself, the serious conduct with which the moved educational process, the good didactic material elaborated and demanded, besides the peculiar characteristics of people involved with History undergraduate course. About the weaknesses, there were the marks of implantation phase, including with the evaluation process and the faulty and deficient communicational system. The most important findings of this study were: this degree contributed to the technical and cognitive training of its graduates, but left some shortcomings regarding their professional training. He trained, however, reflective teachers, able to advance about what lacked in his academic training.The graduates, who were fruits of history academic training in the distance learning modality of UFS, have been involved as human and professional, capable of using their teaching abilities to transform lives of others also through Education. They changed their world vision way, deal with the diverse and improved their quality of life. The thesis of this work considers, with regard to the training of the subjects involved in this study, the History undergraduate course in this modality, despite the challenges faced during the training journey, that it was able to prepare well its graduates and affected positively their lives, in several aspects: personal, professional, social and economic._________________________________________________________________________________________